2013
DOI: 10.12688/f1000research.2-34.v2
|View full text |Cite
|
Sign up to set email alerts
|

Verbal and novel multisensory associative learning in adults

Abstract: To date, few studies have focused on the behavioural differences between the learning of multisensory auditory-visual and intra-modal associations. More specifically, the relative benefits of novel auditory-visual and verbal-visual associations for learning have not been directly compared. In Experiment 1, 20 adult volunteers completed three paired associate learning tasks: non-verbal novel auditory-visual (novel-AV), verbal-visual (verbal-AV; using pseudowords), and visual-visual (shape-VV). Participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…Consistent with the findings of Fifer et al. (), children and adults performed best on the verbal‐AV task, but unlike adults, children did not show a generalized multisensory advantage for novel multisensory stimuli. Although, all three associative learning tasks significantly correlated with IQ, only the d‐prime measure on the verbal‐visual associative task was identified as a unique predictor of FSIQ scores, suggesting that general intellectual abilities in children may be related to multisensory verbal associative learning abilities.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Consistent with the findings of Fifer et al. (), children and adults performed best on the verbal‐AV task, but unlike adults, children did not show a generalized multisensory advantage for novel multisensory stimuli. Although, all three associative learning tasks significantly correlated with IQ, only the d‐prime measure on the verbal‐visual associative task was identified as a unique predictor of FSIQ scores, suggesting that general intellectual abilities in children may be related to multisensory verbal associative learning abilities.…”
Section: Discussionsupporting
confidence: 88%
“…The generalized novel multisensory learning advantage (relative to unisensory incidental learning) found in adults by Fifer et al. () was not evident in children. This finding is consistent with other studies that have shown immaturities in different types of multisensory learning, such as visual‐haptic learning and incidental learning of auditory‐visual object categories, throughout childhood (Broadbent et al., ; Pirogovsky, Murphy, & Gilbert, ).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations